Azospirillum brasilense INOCULATION IMPROVES THE MORPHOPHYSIOLOGICAL ASPECTS OF MAIZE IN SOILS WITH HIGH AND LOW NITROGEN CONTENTS: Maize inoculated with A. brasilense under nitrogen variation - Daniele Maria Marques; Paulo César Magalhães; Ivanildo Evódio Marriel; Adriano Bortolotti da Silva; Lorena Gabriela Almeida; Thiago Corrêa de Souza (REVISTA BRASILEIRA DE MILHO E SORGO, 2024)
The objective of this research was to evaluate the morphophysiology, root system and biomass in maize plants inoculated by A. brasilense at two nitrogen doses in the soil. The experiment was carried out in a greenhouse using a completely randomized design. A dose that guaranteed N120 grain yield (120 kg ha-1) and another that reduced N20 availability by 100% (20 kg ha-1) was stipulated. The inoculant used was a mixture of two homologous A. brasilense strains, Az1 (CMS 7+1626) and Az2 (CMS 11+1626). The treatments consisted of a combination of nitrogen doses and inoculation by A. brasilense, with four replications. Root morphology, nitrate and arginase reductase, pigment content, height and leaf area were evaluated. Inoculation by A. brasilense Az1 and Az2 increases root volume and specific length. Nitrate reductase and arginase activities in the soil were higher with A. brasilense, as well as chlorophylls, height and leaf area at 20 kg ha-1 nitrogen in the soil. At 120 kg ha-1 nitrogen, A. brasilense also increases specific root length and nitrate reductase activity, resulting in greater maize height and leaf area. A. brasilense favors the exploration of the soil profile for the absorption of water and nutrients. Inoculation improves the morphophysiology of maize in low soil nitrogen, but does not reduce the use of nitrogen fertilizers in this crop. Inoculation by A. brasilense is an efficient, ecological and low-cost technology that contributes to the sustainability of maize production.